Correlation Analysis of Landslide Disaster with Land Tenure (Case Study: Wonosobo Regency) - Luthfina, Muhammad Annis Wichi; Hernandi, Andri (Journal of Science and Applicative Technology, 2024)
Indonesia is a country that often experiences various kinds of natural disasters, one of which is landslides. Wonosobo Regency is a district that is prone to landslides considering its geographical conditions with steep slopes and high rainfall. Landslides are disasters that are directly related to changes in soil and soil conditions. This is unconsciously related to land rights, one of which is land tenure. In this research, a correlation study was conducted to determine the relationship between the level of knowledge about landslides and the level of knowledge about land tenure. The test uses the Spearman rank test. The result of this research is that there is a relationship between the level of knowledge about landslides and the level of knowledge about land tenure.